Improved Agilla Middleware Architecture to Increase the Efficiency of Wireless Sensor Networks - V P, Ms Priyanka; Pramilarani, Ms K. (IJRDO -Journal of Computer Science Engineering, 2016)
Wireless Sensor Network (WSN) consists of number of sensor nodes whichcommunicate with each through sensors, where each node consists of sensor, processor andmemory. The main aim of wireless sensor network is to reduce the energy consumption andincrease speed. For the design and implementation of wireless sensor networks middlewaretechnology Agilla is used. In three tier client server architecture middle tier is called asmiddleware and is placed between client and server. Middleware help to bridge the gapbetween high level application and under the control of the operations of Wireless SensorNetworks. Agilla is mobile agent based middleware run on TinyOS. Application programsare composed of agents, which be transmitted across the nodes. Each node could supportmultiple autonomous agents and maintains a neighbour list and tuple space. The agents aretransmitted to build an application by following neighbour list. With multiple autonomousagents, it allows multiple users from different applications share the networksimultaneously. Agilla has good performance on reliability